Enhancing trauma cardiopulmonary resuscitation simulation training with the use of virtual reality (Trauma SimVR): Protocol for a randomized controlled trial - Josef Michael Lintschinger; Philipp Metelka; Lorenz Kapral; Florian Kahlfuss; Lena Reischmann; Alexandra Kaider; Caroline Holaubek; Georg Kaiser; Michael Wagner; Florian Ettl; Leonhard Sixt; Eva Schaden; et al. (PLoS ONE, 2025)
Background With the increasing availability and use of digital tools such as virtual reality in medical education, there is a need to evaluate their impact on clinical performance and decision-making among healthcare professionals. The Trauma SimVR study is investigating the efficacy of virtual reality training in the context of traumatic in-hospital cardiac arrest. Methods and analysis This study protocol (clinicaltrials.gov identifier: NCT06445764) for a single-center, prospective, randomized, controlled trial focuses on first-year residents in anesthesiology/intensive care, traumatology, and emergency medicine. The study will compare the clinical performance in a simulated scenario between participants who received virtual reality training and those who received traditional e-learning courses for preparation. The primary endpoint is the time to a predefined intervention to treat the underlying cause of the simulated traumatic cardiac arrest. Secondary endpoints include protocol deviations, cognitive load during simulated scenarios, and the influence of gender and personality characteristics on learning outcomes. The e-learning and the virtual reality training content will be developed in collaboration with experts from various medical specialties and nursing, focusing on procedural processes, guideline adherence specific to trauma patient care, and traumatic in-hospital cardiac arrest. Results The results of this study will provide valuable insights into the efficacy of virtual reality training, contributing to the advancement of medical education, and serve as a foundation for future research in this rapidly evolving field.